Le jardin individuel au cœur des enjeux fonciers et écologiques dans une métropole régionale : le cas de Tours en France - Pascal Oillic (Éditions en environnement VertigO, 2012)
This work is an attempt to capture the changing role of green spaces and structure of cities they lead through the soil, taken here in both its horizontal, land component, and in its verticality, living entity. The soil is the support for parks, a major land tenure issue, but also a social and environmental investment. The study focuses on an average size town, Tours, characterized as a green city and more precisely on Saint-Cyr-sur-Loire, a leafy and wealthy suburb, filled with green spaces, most of them privately owned. Based on interviews with associations, residents and city officials, this research shows that individual gardens are the mediators between soil, users and municipality. The spatial practices of residents in the gardens are at the heart of their relationship to the soil as a living entity. Representations of nature that motivate them are mostly that of a recreational area where the soil is seen as a constraint leading to a variety of adapted strategies.